PENERAPAN MEDIA PEMBELAJARAN BERBASIS GOOGLE EARTH PADA SISWA SDN BRINGINBENDO 1 DALAM MENINGKATKAN MINAT BELAJAR SISWA - Orta Rosinda Putra; Muhammad Yusron Maulana El Yunusi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Effective education requires interesting and innovative learning methods to increase students' interest in learning during the learning process. One technology that can be utilized is Google Earth, which offers an interactive visual experience, 3D, Virtual Tour. This study was conducted at SDN Bringinbendo 1 to explore the application of Google Earth-based learning media in increasing students' interest in learning. This study aims to analyze the effect of using Google Earth-based learning media on students' interest in learning at SDN Bringinbendo 1 Taman Sidoarjo. By utilizing descriptive qualitative methods and using observation and interview techniques, this study focuses on how technology-based media can improve students' understanding in learning the concepts of geography, topography, landscapes and other social sciences. The use of Google Earth as an interactive media provides realistic visualization and makes it easier for students to get to know their surroundings. The results of the study indicate that Google Earth media is effective in increasing students' interest and involvement in learning.